The role of international tourism, trade openness and renewable energy in the financial development of selected African countries - Solomon Aboagye; Paul Adjei Kwakwa (Research in Globalization, 2023)
It is well established that financial development is pivotal to the proper functioning of the real economy and there is a vast body of literature investigating into its determinants. In this study, we shift attention to tourism and renewable energy consumption that are rarely discussed in the financial development debate along with trade openness. Even though, tourism and renewable energy consumption may be less conventional to issues of financial intermediation, they could, along with trade openness, nonetheless contribute to some aspects of financial development in ways consistent with the finance-growth hypothesis. Consequently, this study, while controlling for economic growth, development assistance and government expenditure examines the effects of renewable energy consumption, tourism development and trade openness on financial development in selected African countries. The study relies on data from the World Bank (2023) World Development Indicators for seven African countries (Egypt, Tunisia, Kenya, South Africa, Zimbabwe, Ivory Coast and Morocco) over the periods 1995-2021. Fully Modified Ordinary Least Square (FMOLS) regression estimations reveal that, in the long run, trade openness, international tourism, and renewable energy stimulate financial development. The quantile regression which rendered additional support to this evidence further reveals that, the financial sector gains associated with trade openness, international tourism and renewable energy are greater for countries with lower financial sector development. Thus, a country can still optimize the gains associated with increased trade openness, international tourism, and renewable energy consumption with a relatively less developed financial market. Hence, polices that improve tourism development, promote renewable energy consumption and intensify economic openness may be important catalysts for stimulating further financial development in Africa.
Keywords: 330; Financial development; Financial markets; Renewable energy; Tourism; Trade openness